CONSTRUCTION AND DECONSTRUCTION OF POLITICAL IDEOLOGY THROUGH DIGITAL MEDIA DISCOURSE IN PAKISTAN: A CRITICAL DISCOURSE ANALYSIS OF FACE BOOK POSTINGS - Samreen Riaz Ahmed; Ammara Zafar; Shazia Naseer; Muhammad Rashid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Statesmen have been using political rhetoric to spread ideas for as long as humanity has existed. The rise of Critical Discourse Analysis (CDA) has allowed for the exposure of concealed ideologies in political discourse. This theory supports the use of linguistics and semiotic elements to understand conversation from a micro to macro level. The current research also considers the analysis of political postings on social media for the objective of exposing concealed political speech in text and semiotics. The political discourse analysis (PDA) covers a wide range of topics, including the exposition and explanation of hidden messages, the building and deconstruction of ideology, and the manipulation of public opinion. Pakistan has always been caught in a truth conundrum when it comes to the policies and ideology espoused by political parties. In this perspective, the current study is extremely important to conduct due to the increased temperature of political ideology building following the 2018 elections and the effect of social media. The study's sample includes posts from the political pages of the ruling PTI (Pakistan Tehreek-e-Insaf) and the opposition PML-N (Pakistan Muslim League Nawaz), which is playing the role of opposition party. Five posts from each page are chosen as the study's sample. For the analysis of the postings, Fairclough (2003) and Van Dijik (2009) CDA models are used. The study's findings show that the discourse on Facebook is both deep and high pragmatic, with the goal of deconstructing political ideologies in people's minds through the use of various terms appropriate to the situation, such as price increases, corruption, illegal use of power, poverty and ineffective administration, and foreign relations, among others. The type of discourse used in Facebook posts has the goal of drawing people's attention to certain types of ideas in a legitimate way, as the speakers are well-wishers of the public, while the resistance is expressed by the public figure page in common man's language, but full of similes and exemplifications.